Evaluative methodological proposal in the performance of the teaching learning process in the university policlinic - Maricel Castellanos González; Jorge Cañellas Granda; Mikhail Benet Rodríguez; Luis Senén Rodríguez Fernández (Medisur)
Background: The university policlinic should become into a center of remarkable health assistance to the population and a model for the basic and post graduated formation of the health professionals. Objective: To propose a methodology to assess the quality in the implementation of the teaching learning process of the new model in the formation of the general comprehensive doctor. Method: The diagnosis of the variables as well as the quality indicators to be taken into account was carried out. The instruments to be used for the evaluation of the implementation in the teaching learning process of this new pedagogical model were proposed. The methodology of the designed evaluation is focused on the knowledge of how planning, execution of the process, functional and organizable aspects, organizable environment, as well as satisfaction of professors, students, leaders are developed in these new places of formation. Results: The elaborated methodological proposal is integrated and has a systemic approach based on a paradigm of mixed evaluation with a holistic model directed to the dimension of efficacy. The variables to assess are considered within the levels of institutional, group, and individual analysis. Conclusions: The strategy will provide information about the quality and the factors that can be influencing the efficacy of the teaching learning process throughout the analysis and operation of the proposed indicators.